65 Management of early-onset scoliosis in patients with Prader Willi syndrome with magnetic growth rods – a case series review. (30th November 2020) - Bowyer, Henry; Amiri, Amir; Harris, Mark
Abstract : Background: Prader Willi syndrome (PWS) is a rare genetic disorder characterised by developmental delay and hyperphagia. It is strongly associated with scoliosis, largely attributed to hypotonia and ligamentous laxity. Management of scoliosis in these patients can be challenging due to early onset of disease, higher BMI, poor bone quality and poor brace compliance. Skin picking behaviours may also have a significant impact on poor healing. Magnetic Expansion Control growing rods (MAGEC) have become the surgical management of choice in some patients with progressive early-onset scoliosis, however there have been no published reports on their use in the PWS population. Here we report our experience of treating children with PWS with MAGEC rods. Methods: A retrospective review of children with PWS who underwent MAGEC rod insertion between March 2010 to March 2020 at a quaternary paediatric hospital. Spinal column distraction was measured between the proximal and distal vertebrae in which fixations were inserted. Results: 4 patients with PWS had MAGEC rod inserted during the study period. All had undergone MRI imaging prior to surgery. Median age at primary operation was 5.5 years. All patients were overweight at time of primary operation (median BMI 94.5th centile). A total of 11 MAGEC rods were used of which 5 had reported instrumentation failures (45%). These included 2 pin fractures and 3 proximal construct pull-outs. 2 of the patients developed post-operative infection requiring surgical intervention with 1 undergoing removal of metalwork. Overall a median of 4.3 mm (IQR=1.1–25.3) of spinal distraction was achieved either prior to definitive spinal fusion or at last follow-up with median distraction per year of MAGEC of 1.1 mm (IQR=0.5–5.1). Conclusion: Management of early onset scoliosis in patients with PWS using MAGEC rods is challenging and can be associated with a high complication rate. Limited spinal growth was observed amongst this cohort.